2023
DOI: 10.1101/2023.01.05.522847
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Label-free high-resolution infrared spectroscopy for spatiotemporal analysis of complex living systems

Abstract: Label-free chemical and structural imaging of complex living tissue and biological systems is the holy grail of biomedical research and clinical diagnostics. The current analysis techniques are time-consuming and/or require extensive sample preparation, often due to the presence of interfering molecules such as water, making them unsuitable for the analysis of such systems. Here, we demonstrate a proof-of-principle study using label-free optical photothermal mid-infrared microspectroscopy (O-PTIR) for fast, di… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…[32][33][34] However, due to the low thermo-optic coefficients of water and protein (dn/dT: ~9 x 10 -5 and ~1.4 x 10 -4 , respectively), OPTIR applies high-intensity tightly-focused probe-beam irradiation for detection, which could induce thermal stress and photo-oxidative damage of cells over long exposure. 35,36 Unlike conventional optical microscopy, Mid-infraRed Optoacoustic Microscopy (MiROM) is a positive-contrast modality that allows label-free spectral imaging of biomolecules in living cells by detecting optically-generated ultrasound waves that increase in intensity as optical absorption increases. 37 We have previously demonstrated that MiROM affords higher sensitivity than Raman microscopy in the fingerprint spectral region (1800 -900 cm -1 ) but, until now, proteins have been detected mainly by using the amide II band (1600 -1500 cm −1 ) mainly associated with C-N stretching and N-H bending vibrations.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34] However, due to the low thermo-optic coefficients of water and protein (dn/dT: ~9 x 10 -5 and ~1.4 x 10 -4 , respectively), OPTIR applies high-intensity tightly-focused probe-beam irradiation for detection, which could induce thermal stress and photo-oxidative damage of cells over long exposure. 35,36 Unlike conventional optical microscopy, Mid-infraRed Optoacoustic Microscopy (MiROM) is a positive-contrast modality that allows label-free spectral imaging of biomolecules in living cells by detecting optically-generated ultrasound waves that increase in intensity as optical absorption increases. 37 We have previously demonstrated that MiROM affords higher sensitivity than Raman microscopy in the fingerprint spectral region (1800 -900 cm -1 ) but, until now, proteins have been detected mainly by using the amide II band (1600 -1500 cm −1 ) mainly associated with C-N stretching and N-H bending vibrations.…”
Section: Introductionmentioning
confidence: 99%